PENGARUH LATIHAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA TANGAN TERHADAP HASIL SHOOTING FREE THROW PADA TIM BASKET SMA NEGERI 15 LUWU - Fadhya Astuti; Suaib Nur; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of arm muscle strength training and hand-eye coordination exercises on free throw shooting performance in the basketball team of SMA Negeri 15 Luwu. The research employed an experimental method with a two-group pretest-posttest design. The sample consisted of 24 students, divided into two groups: Group A underwent arm muscle strength training, while Group B performed hand-eye coordination exercises, with a training frequency of 16 sessions. The instrument used was a free throw shooting test conducted with a basketball hoop within the designated shooting area. Data analysis revealed that both types of training had a significant effect on improving free throw shooting performance. Based on the paired sample t-test, a significance value of p < 0.05 was obtained for both groups. Furthermore, the independent sample t-test showed no significant difference between Group A and Group B (p = 0.572). Therefore, it can be concluded that arm muscle strength training and hand-eye coordination exercises do not differ significantly in enhancing free throw shooting performance.